Voltammetry Determination of Cefotaxime on Zinc Oxide Nanorod Modified Electrode - Vasantharaghavan, Vanitha; Cingaram, Ravichandran (Current Pharmaceutical Analysis, 2021)
Background: The Glassy Carbon Electrode (GCE) was modified with zinc oxide nanoparticles to enhance the electrocatalytic activity of the redox behavior of cefotaxime ion. ATOMIC Force Microscopy (AFM) photographic studies showed the nanorod like structure of the zinc oxide, which was coated uniformly on the electrode surface. Methods: The zinc oxide nanorod modified electrode was used as novel voltammetric determination of cefotaxime. The results of voltammetric behavior are satisfactory in the electro oxidation of cefotaxime, and exhibit considerable improvement compared to glassy carbon electrode. Results: Under the optimized experimental conditions, the ZnO nanorod modified electrode exhibit better linear dynamic range from 300 ppb to 700 ppb with lower limit of detection 200 ppb for the stripping voltammetric determination of cefotaxime. Conclusion: The pharmaceutical and clinical formulation of cefotaxime was successfully applied for accurate determination of trace amounts on ZnO nanomateials modified electrode.
Keywords: voltammetry